FATORES QUE INFLUENCIAM A MOTIVAÇÃO DOS DISCENTES NAS AULAS DE EDUCAÇÃO FÍSICA - de Araujo Bezerra, Francelia; de Araújo Lima, Gecileia; Araújo de Souza, Germano; Dantas Carvalho, Gabriela (Revista Form@re - Parfor/UFPI, 2026)
.